2016
DOI: 10.3892/mmr.2016.5545
|View full text |Cite
|
Sign up to set email alerts
|

Functional study of the upregulation of miRNA-27a and miRNA-27b in 3T3-L1 cells in response to berberine

Abstract: Berberine is the major active component of Rhizoma Coptidis derived from a traditional Chinese herbal medicine and is known to regulate micro (mi)RNA levels, although the mechanism for this action remains unknown. The present study confirmed that treatment of 3T3‑L1 cells with berberine inhibited cell viability and differentiation in a dose‑ and time‑dependent manner, and significantly increased the mRNA expression levels of miRNA‑27a and miRNA‑27b. In addition, in 3T3‑L1 cells treated with berberine, overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…proved that Gal-3 had a direct interaction with PPARγ and modulated its transcriptional activity 11 . Intriguingly, there were reports showed that in 3T3-L1 adipocytes, PPARγ was a target of both let-7d 32 and miR-27a 21 , and BBR was able to up-regulate these miRNAs, as proved by our results and a previous study 21 . Whether or not miR-27a is involved in the modulation of Gal-3 is currently unclear.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…proved that Gal-3 had a direct interaction with PPARγ and modulated its transcriptional activity 11 . Intriguingly, there were reports showed that in 3T3-L1 adipocytes, PPARγ was a target of both let-7d 32 and miR-27a 21 , and BBR was able to up-regulate these miRNAs, as proved by our results and a previous study 21 . Whether or not miR-27a is involved in the modulation of Gal-3 is currently unclear.…”
Section: Discussionsupporting
confidence: 81%
“…In human subjects with non-alcoholic fatty liver disease (NAFLD) and obesity, BBR effectively reduced body weight, body mass index (BMI), and waist 17 . In accordance with the anti-obesity effect, BBR inhibited the differentiation and proliferation of 3T3-L1 adipocytes, as indicated by the reduction of lipid accumulation, the down-regulation of adipogenic genes, and the inhibition of DNA synthesis 1,1821 .…”
Section: Introductionmentioning
confidence: 59%
“…Berberine (Ber) is an isoquinoline alkaloid compound extracted from Rhizoma Coptidis, which has a wide range of biological effects and can regulate miRNA levels (Wu et al, ). Our previous study found that adding Ber into embryo culture medium elevated the anti‐apoptotic gene miR‐21 in pre‐implantation mouse embryos (Zhang et al, ), significantly promoted the pregnancy rate and survival rate of a litter upon in vitro cultured blastocyst transfer (Gao, Fu, Chen, Mu, & Su, ), decreased the lipid droplet content in porcine oocytes, promoted oocyte maturation in vitro (Luo et al, ; Zhang et al, ), and increased the blastocyst rates of parthenogenetic activation embryos and in vitro fertilization (IVF) embryos, and increased the number of inner cell mass (ICM) and total cells in pig blastocysts, decreased the apoptosis index,improved the level of NO in culture environment, inhibited MDA production, and reduced the damage of free radical to embryos (Xu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, BBR also has protective effects against obesity, steatotic liver and insulin resistance. It inhibits cell viability, cell differentiation, and triglyceride content in a dose- and time-dependent manner, through marked induction of miR-27a and miR-27b; while miR-27a and miR-27b inhibitors can counteract this repressive function of BBR (Wu et al, 2016). Steatotic liver results from disordered lipid metabolism, where lncRNA MRAK052686, NRF2 (Yuan et al, 2015), and miR-373 (Li C. H. et al, 2018) are down-regulated.…”
Section: Pro-apoptosis Effects Of Chmsmentioning
confidence: 99%